2021
DOI: 10.1073/pnas.2023123118
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity to geometric shape regularity in humans and baboons: A putative signature of human singularity

Abstract: Among primates, humans are special in their ability to create and manipulate highly elaborate structures of language, mathematics, and music. Here we show that this sensitivity to abstract structure is already present in a much simpler domain: the visual perception of regular geometric shapes such as squares, rectangles, and parallelograms. We asked human subjects to detect an intruder shape among six quadrilaterals. Although the intruder was always defined by an identical amount of displacement of a single ve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
60
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 69 publications
(66 citation statements)
references
References 55 publications
6
60
0
Order By: Relevance
“…As also proposed by others, only humans would possess a recursive compositional capacity (Dehaene et al, 2015;Fitch, 2014;Hauser et al, 2002;Penn et al, 2008). Our recent work (Sablé-Meyer et al, 2021) shows that, for quadrilaterals, human behavior differs strikingly from baboons and is characterized by a symbolic geometrical regularity effect: in humans only, regular quadrilaterals (which can be compressed in the present language) are easier to perceive than less regular ones. Importantly, in this work, baboon behavior was not random, but could be captured by models of the ventral visual pathway for object recognition.…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…As also proposed by others, only humans would possess a recursive compositional capacity (Dehaene et al, 2015;Fitch, 2014;Hauser et al, 2002;Penn et al, 2008). Our recent work (Sablé-Meyer et al, 2021) shows that, for quadrilaterals, human behavior differs strikingly from baboons and is characterized by a symbolic geometrical regularity effect: in humans only, regular quadrilaterals (which can be compressed in the present language) are easier to perceive than less regular ones. Importantly, in this work, baboon behavior was not random, but could be captured by models of the ventral visual pathway for object recognition.…”
Section: Discussionsupporting
confidence: 65%
“…Cognitive tests performed in relatively isolated human groups such as the Mundurucu from the Amazon, the Himba from Namibia, or aborigine groups from Northern Australia, show that in the absence of formal education in mathematics, adults and even children already possess strong intuitions of numerical and geometric concepts (Amalric et al, 2017;Butterworth et al, 2008;Dehaene et al, 2006;Izard et al, 2011b;Pica et al, 2004;Sablé-Meyer et al, 2021). (Amalric et al, 2017;Butterworth et al, 2008;Dehaene et al, 2006;Izard et al, 2011b;Pica et al, 2004; Indeed, those uneducated adults and children share a large repertoire of abstract geometric concepts (Dehaene et al, 2006) and use them to capture the regularities in spatial sequences (Amalric et al, 2017) and quadrilateral shapes such as squares or parallelograms (Sablé-Meyer et al, 2021). They even possess sophisticated intuitions of how parallel lines behave under planar and spherical geometry, such as the unicity of a parallel line passing through a given point on the plane (Izard et al, 2011a).…”
Section: Human and Animal Sensitivity To Geometric Patterns: A Brief Reviewmentioning
confidence: 99%
“…In adults, reasoning on mathematical objects or on factual knowledge recruits different regions, covering a dorsal frontal-parietal pathway, contrasting with the classical perisylvian linguistic network ( Monti, et al., 2012 ; Monti and Osherson, 2012 ; Amalric and Dehaene, 2019 ; Reverberi, et al., 2007 ). The adult sophisticated mathematical abilities are grounded in the parietal areas ( Amalric and Dehaene, 2016 ), building upon a set of proto-mathematical abilities observed since birth and associated with approximate numerosity ( Izard, et al., 2009 ) and probably also simple geometry ( Sablé-Meyer, et al., 2021 ). The type of calculations these regions support rapidly outperform what has been witnessed in non-human animals.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the average K-complexity of a stream is divided by 6.25 thanks to compression (see Fig 5). Recent data ( Planton et al, 2021 ; Al Roumi et al, 2020 ; Sablé-Meyer et al, 2021, 2022 ) showed that humans’ performances were highly sensitive to stimuli compressibility, arguing for a compressed encoding of inputs. Thus, the extraction of high-order structures could be at the basis of a human abstract compressed language of thought ( Fodor, ???? )…”
Section: Discussionmentioning
confidence: 99%